Combining explicit and implicit interaction modes with virtual characters in public spaces - Ribeiro, Pedro (2010)
Improving the visiting experience of exhibitions and public spaces in general has been the subject of several studies over the past years. In the study presented here, we were particularly interested in understanding the potential of combining explicit and implicit interaction modes between virtual characters and visitors. We present in this paper scenarios that exemplify the combination of these interaction modes, and an initial study with user involvement, based on a software platform that we are currently developing. We report on first feedback from users about the system-level interaction, usability, and visiting experience. The tested case study should create a sense of ubiquity of the virtual characters throughout the visit, and take advantage of their communication skills, at the same time giving freedom to visiting groups to interact with each other and to make visits to the exhibition place at the order they desire.